Rates of other‐cause mortality after radical cystectomy are decreasing over time—A population‐based analysis over two decades. Issue 8 (4th April 2020) - Rosiello, Giuseppe; Knipper, Sophie; Palumbo, Carlotta; Pecoraro, Angela; Luzzago, Stefano; Deuker, Marina; Stolzenbach, Lara F.; Tian, Zhe; Gallina, Andrea; Gandaglia, Giorgio; Montorsi, Francesco; Shariat, Shahrokh F.; et al.
Abstract: Background and Objectives: To investigate other‐cause mortality (OCM) rates over time according to several baseline characteristics in bladder cancer (BCa) patients treated with radical cystectomy (RC). Methods: Within the Surveillance, Epidemiology, and End Results database (1988‐2011), we identified 7702 T1‐2 N0 M0 urothelial BCa patients treated with RC. Temporal trends and multivariable Cox regression (MCR) analyses assessed 5‐year OCM. Data were stratified according to the year of diagnosis (1988‐1995 vs 1996‐2000 vs 2001‐2004 vs 2005‐2008 vs 2009‐2011), age group (<60 vs 60‐75 vs >75 years), sex, race, marital status, and socioeconomic status. Results: Overall, OCM rates decreased from 13.9% in 1988‐1995 to 8.6% in 2009‐2011. The greatest decrease was recorded in elderly (>75) patients (32%‐16%, slope: −0.55% per year; P  = .01), followed by patients aged 60 to 75 (21%‐5%, slope: −0.35% per year; P  = .01), unmarried patients (16%‐10%, slope: −0.26% per year; P  < .001), male patients (14%‐8.9%, slope: −0.23% per year), and African Americans (16%‐11%, slope: −0.27% per year; P  < .001). MCR models corroborated these results. Conclusions: Most important decrease in OCM after RC over the last decades was recorded in the elderly, unmarried, and male patients. Nonetheless, these three patient groups still represent ideal targets for efforts aimed at minimizing the morbidity and mortality after RC, as their risk of OCM is higher than in others.